Where both ends meet a study of intercultural communication in the work setting and how it affects workers' satisfaction towards work - Federico, Pierre Angeline R.
This is a study of the communication patterns and the degree of cultural familiarity between non-Filipino managers and local workers at CEPZ in Rosario, Cavite, and how these affect workers' satisfaction towards work. It is both a quantitative and a qualitative study. The study used the survey and focus interviews as its major research methods. One hundred twelve (112) respondents participated in the survey while five informants served as the pool of qualitative information. Results showed that the socio-demographic profile of respondents are the following: majority are females, in their late teens up to late twenties, are college graduates of at least have reached tertiary level, are members of the staff and have stayed in their respective companies for six years or less. Informants, on the other hand, are mostly Japanese, are managers in their respective companies for less than eight years. Workers consider interactions as mostly manager-initiated. Managers, on the other hand, hold divergent views: half believed the interactions as manager-initiated while the other half thought that both sides can start communication. Reports and meetings emerged in the survey as the most common forms of communication between the two parties. This validates the claim of the informants. Both sides thought that technical/work-related matters are the most talked-about by heads and subordinates. Similarly, both agreed on the frequency of interactions, which is daily. Communication issues appeared as the primary problem of local workers and non-Filipino managers in relating with one another. Specific communication issues involved language inefficiency of both parties. Although verbal communication might have been the deterrent, some members in both parties relied partly on non-verbal communication in helping "getting messages across" to the other. Most members of both groups were unfamiliar with the culture of the other but many on both groups were eager to learn each other's culture. Both parties have positive perceptions towards one another and almost three-quarters of the survey population are satisfied with their work. Lastly, an overwhelming response from subjects thought that there is a relationship between the state of communication and degree of cultural familiarity with workers' satisfaction towards work. On the same note, informants believed that effective communication is important in satisfying the needs of local workers.